TOXICITY TEST OF MAKUTADEWA (Phaleria macrocarpa (Scheff.)Boerl.) BARK AGAINST Artemia salina Leach AND THIN LAYER CHROMATOGRAPHY PROFILE OF THE ACTIVE FRACTION - Triana Hertiani; Silvia Utami Tanjung Pratiwi (Indonesian Journal of Pharmacy, 2002)
Makutadewa (Phaleria macrocarpa (Scheff) Boerl.) is one of the herbal medicines used against cancer, however, the scientific basis of the activity still void. Daphne mezereum, the same family (Thymelaeaceae) to makutadewa has been proved to contain cytotoxic substances in its bark. Therefore, the aims of this research were to investigate the toxic effect of makutadewa bark against Artemia salina Leach. as the primary step to identify an anticancer activity and find out substances responsible to this activity. The material powder was extracted using Soxhlet apparatus with chloroform, followed by methanol and finally by distilled water. The toxicity of chloroform, methanolic and aqueous extracts were assayed against A.salina Leach. The chloroform extract (most active) with the LC50 of 29.6  0.14 g/ml was fractionated by vacuum liquid chromatography using wash benzene 100 % (a); wash benzene-ethyl acetate =20:1 (b); 15:1 (c); 10:1 (d); 5:1 (e); 2:1 (f) and chloroform-methanol 1:1 (g) as mobile phases. The active fractions against A.salina were E {combination of (e) and (f)} with LC50 of 106,9 g/ml and F (g) with the LC50 of 131,53 g/ml, hence less toxic than the original extract. The thin layer chromatogram profiles showed that E and F fractions contained terpenoid and alkaloid substances.Key words: toxicity test, (Phaleria macrocarpa (Scheff)Boerl.), bark